2018
DOI: 10.1371/journal.pone.0201352
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward UNAIDS 90-90-90 targets: A respondent-driven survey among female sex workers in Kampala, Uganda

Abstract: BackgroundWe investigated progress towards UNAIDS 90-90-90 targets among female sex workers in Kampala, Uganda, who bear a disproportionate burden of HIV.MethodsBetween April and December 2012, 1,487 female sex workers, defined as women, 15–49 years, residing in greater Kampala, and selling sex for money in the last 6 months, were recruited using respondent-driven sampling. Venous blood was collected for HIV and viral load testing [viral load suppression (VLS) defined as <1,000 copies/mL]. We collected data us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The 90–90-90 targets are due in 2020, and appear unlikely to be met across the board in Uganda, with low rates of detection, treatment and suppression in particular high risk populations [ 16 ]. Thereis an imperative then to optimise testing and counselling protocols, which currently offer no specific guidance in relation to mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 90–90-90 targets are due in 2020, and appear unlikely to be met across the board in Uganda, with low rates of detection, treatment and suppression in particular high risk populations [ 16 ]. Thereis an imperative then to optimise testing and counselling protocols, which currently offer no specific guidance in relation to mental health.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is significant variation between different segments of the population. For example, a study with female sex workers found of the 31.4% of the sample who were HIV positive, just 45.5% knew their status, 37.8% self-reported they were on HIV treatment, and 35.2% were virally suppressed [ 16 ]. There are issues in relation to linkage into care, with studies reporting suboptimal rates of people starting anti-retroviral medications and staying in HIV care.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, only 52% of adults in sub-Saharan Africa (SSA) who were living with HIV and on antiretroviral therapy (ART) had achieved virological suppression 2. High HIV prevalence in SSA particularly among key populations including female sex workers (FSWs) poses a major challenge to achieving the targets 3. The critical factors for improving health outcomes of people living with HIV and stopping onward transmission are early ART initiation accompanied by sustained virological suppression 4.…”
Section: Introductionmentioning
confidence: 99%
“…According to a 2014 global review, approximately 42% of all FSW living with HIV were receiving ART [8]. Among all FSW living with HIV in Kampala, Uganda, 37.8% were on ART and 35.2% were virally suppressed [26]. In Zimbabwe, 43.3% of all FSW living with HIV were on ART and 49.5% were virally suppressed, compared to 66.4% and 58.2% among general population women, respectively [6,27].…”
Section: Antenatal Care (Anc) Uptake and Hiv Testingmentioning
confidence: 99%